ANALISIS KEMAMPUAN MEMBACA NYARING DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS 3 SDN PETERONGAN SEMARANG - Olyvia Tri Herawati; Mudzanatun; Qoriati Mushafanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading aloud is a fundamental skill in Indonesian language learning that is crucial for improving students' reading fluency and comprehension. This study aims to describe the planning, implementation, and reading-aloud proficiency of third-grade students at SDN Peterongan Semarang. The study employs a qualitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that the teacher effectively planned and conducted reading-aloud lessons by preparing lesson plans, selecting appropriate texts, and modeling correct reading techniques. Overall, the students demonstrated good reading-aloud proficiency regarding pronunciation, intonation, volume, fluency, and the use of pauses; however, some students still faced difficulties due to a lack of understanding regarding punctuation, limited vocabulary, and insufficient practice. Therefore, more regular practice is required to enhance the students' reading-aloud skills.